Hadith #4289 - Sunan Abi Dawud - Abu Ishaq al-Sabay'ai' أبو إسحاق السبيعي عمرو بن عبد الله; al-Mughira ibn Shu'ba; Ali ibn Abi Talib; Amr bin Abi Qays عمرو بن أبي قيس الرازي الأزرق كوفي; Suh'aib bin Khalid al-Bjly شعيب بن خالد البجلي الرازي (Sunan Abi Dawud)
How will a man who comes against his will (be swallowed up by the earth), Messenger of Allah ? He replied: All will be swallowed up, but each will be raised according to his intention on the Day of Resurrection.
Grade: Sahih